ANALISIS KELAYAKAN USAHA PETERNAKAN AYAM PETELUR CLOSED HOUSE - Lambok Rommy Sulaeman; Ade Oki Pebiansyah; Deni Utama; Berliana, Berliana (LPSDI Bina Patria, 2024)
This study aims to analyse the business feasibility of closed house layer farmers. The business feasibility criteria used are: Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Periods. The results of the analysis can be stated that the business of laying hens is feasible or recommended